Radial Variation of Wood Property in Agathis sp. and Pinus insularis Growing at Plantation in Indonesia - Futoshi Ishiguri; Imam Wahyudi; Kazuya Iizuka; Shinso Yokota; Nobuo Yoshizawa (Masyarakat Peneliti Kayu Indonesia, 2010)
To obtain basic knowledge of wood properties in plantation coniferous species growing in tropical countries, the radial variation of wood properties, such as the basic density (BD) and microfibril angle of the S2 layer in tracheid (MFA), and the compressive properties were investigated in 45-year-old Agathis sp. and 32-year-old Pinus insularis growing in Indonesia. In Agathis sp., the BD showed an almost constant value from the pith to the bark. In P. insularis, the BD of heartwood clearly decreased by the extraction with organic solvent. As a result, the BD extracted with organic solvent showed a constant value up to 5 cm from the pith and then gradually increased toward the bark. In the radial variation of the MFA, the highest value was observed near the pith in both species. In the compressive property parallel to the grain, the modulus of elasticity (E) and compressive strength (s) showed an almost constant value from the pith to the bark in Agathis sp., whereas, in P. insularis, both E and s increased from the pith to the bark. In both species, the E was affected by the MFA. In addition, in Agathis sp., s was affected by the BD, while in P. insularis, it was affected by the BD extracted with organic solvent and the MFA.